Boron application in oxisols and responses of coffee plants - Correa, Antonio E.; Pavan, Marcos A.; Miyazawa, Mario (Pesquisa Agropecuaria Brasileira, 2014)
To determine whether plants respond to adsorved or soluble boron, coffee seedlings were grown in two oxisols, Dystrophic Dark-Red Latosol and Dystrophic Dusky Red Latosol, having different boron adsorption capacities. Six solution concentrations were employed: 0.0, 0.5, 1.0, 2.0, 4.0 and 8.0 μg of Bml-1. Four soil boron extraction techniques were evaluated: saturation extract, 0.05 N HCI,0.1 N HCI, and 0.05 N HCI + 0.025 N H2SO4 (Mehlich Solution). Boron proportion was determined by the azomethine-H method. Adsorption of boron by those soils was consistent with a mechanism described by the Langmuir equation, except that deviations occur at solution concentration greater than about 4 μg B/ml. The quantity of boron adsorbed increased with pH. Boron adsorption capacity of the soils has been found to depend on their texture. The saturation extract and 0,05 N HCI extration techniques showed the best correlation with total plant boron uptake. It was found that coffee plants respond only to boron in solution and are not directly influenced by adsorbed boron.